Morphological characteristics and biological cycle of the hoverfly Eristalinus arvorum (Fabricius, 1787) (Diptera, Syrphidae) - Cao, Liang; Zeng, Qing; Ren, Qiuxia; Zeng, Aiping; Zhang, Yongsheng (Frontiers in Sustainable Food Systems, 2022)
The hoverfly Eristalinus arvorum (Fabricius, 1787) (Diptera: Syrphidae), which belongs to the tribe Eristalini, is well known as a pollinating agent for crops and flowering plants in agricultural and natural ecosystems. Although no more information is available about this species, the abundance and floral constancy of this group of hoverflies make E. arvorum an appropriate candidate for use as pollinators and environmental indicator species. However, like most other Eristalinus species, little information has been published on E. arvorum and in-depth studies have yet to be carried out. This research aimed to study the morphology and biological cycle of E. arvorum to improve the artificial rearing system and pollination application. The morphology of eggs, larvae, pupae and adults of E. arvorum were described in detail for the first time. A complete generation of E. arvorum lasts about 30.12±0.14 days, and there is no significant difference in body length between males (10.27±0.29 mm) and females (11.16±0.45 mm). The most noteworthy morphological features of E. arvorum are the stripes of compound eyes, mesonotum, and abdomen of adults, the chorionic structure consisting of fusiform units on the surface of the egg as well as the anterior spiracles and pupal spiracles of pupae.